2011
DOI: 10.1002/hbm.21210
|View full text |Cite
|
Sign up to set email alerts
|

The neuro/PsyGRID calibration experiment

Abstract: Calibration experiments precede multicenter trials to identify potential sources of variance and bias. In support of future imaging studies of mental health disorders and their treatment, the Neuro/PsyGRID consortium commissioned a calibration experiment to acquire functional and structural MRI from twelve healthy volunteers attending five centers on two occasions. Measures were derived of task activation from a working memory paradigm, fractal scaling (Hurst exponent) from resting fMRI, and grey matter distri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 51 publications
2
18
0
Order By: Relevance
“…The level of inter-site comparability is still controversial for conventional MRI data. Some studies demonstrated systematic inter-site differences in structural T1-weighted images, which biased morphometric analyses (Focke et al, 2011), whereas other studies argued that typical pathology-related differences can be detected reliably by, for example, adjusting for potential inter-site differences (Pardoe et al, 2008; Stonnington et al, 2008; Suckling et al, 2012). …”
Section: Introductionmentioning
confidence: 99%
“…The level of inter-site comparability is still controversial for conventional MRI data. Some studies demonstrated systematic inter-site differences in structural T1-weighted images, which biased morphometric analyses (Focke et al, 2011), whereas other studies argued that typical pathology-related differences can be detected reliably by, for example, adjusting for potential inter-site differences (Pardoe et al, 2008; Stonnington et al, 2008; Suckling et al, 2012). …”
Section: Introductionmentioning
confidence: 99%
“…A simpler approach such as applying a voxel‐by‐voxel ANOVA would also be useful to reduce the acquisition site effects [Suckling et al, 2012]. However, SWPCA is a multivariate approach that still offers major advantages over this voxel‐wise algorithm, and similar algorithms have found utility in text document searches [Kriegel et al, 2008; Tavoli et al, 2013; Zhang and Nguyen, 2005].…”
Section: Discussionmentioning
confidence: 99%
“…The study built on the demonstrated proof of concept of the efficacy of minocycline on negative symptoms in two placebo-controlled clinical trials 24,25 in patients on stable APD treatment. Minocycline also lessened weight gain in both RCTs and was well tolerated, with a good safety profile.…”
Section: Rationale For the Benemin Studymentioning
confidence: 99%
“…The chief investigator and research manager at the University of Manchester managed the trial. The academic centres had previously collaborated in the PsyGrid and NeuroPsyGrid consortia, 25 which included four of the six imaging centres that had produced harmonised procedures through their involvement with the NeuroPsyGrid consortium. The sample size was derived from recruitment rates and PANSS scores from the PsyGrid study.…”
Section: Sample Sizementioning
confidence: 99%